2013
DOI: 10.1007/s11999-013-3212-3
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Valgus Stress Radiographs in the Workup for Medial Unicompartmental Arthritis

Abstract: Valgus stress radiographs provided no added benefit to the radiographic assessment of the lateral compartment cartilage and regarding the correctability of the varus deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 27 publications
2
22
0
2
Order By: Relevance
“…Twenty-seven studies comparing different views for knee OA were included. In this context, all studies involving the tibiofemoral compartment considered weightbearing views, both in extension and various degrees of flexion 7 8 10 17 25 118 123 137–147. Studies comparing fully extended and flexed views in general showed a moderate to good agreement between the two projections and similar sensitivity and specificity in detecting cartilage damage, considering arthroscopic findings as reference 117 138 139 148 149.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies comparing different views for knee OA were included. In this context, all studies involving the tibiofemoral compartment considered weightbearing views, both in extension and various degrees of flexion 7 8 10 17 25 118 123 137–147. Studies comparing fully extended and flexed views in general showed a moderate to good agreement between the two projections and similar sensitivity and specificity in detecting cartilage damage, considering arthroscopic findings as reference 117 138 139 148 149.…”
Section: Resultsmentioning
confidence: 99%
“…15,18 Tashiro et al 19 suggested that the mean post-operative limb alignment demonstrated a significantly strong correlation with the values on the pre-operative valgus stress radiographs, while the correlation between both the pre- and the post-operative standing alignment, was moderate. A neutral, or slight under correction is recommended as an ideal post-operative coronal alignment.…”
Section: Discussionmentioning
confidence: 99%
“…If the mechanical axis of the leg was passed at the point from medial 40% to 60% of the knee joint surface on the valgus stress long-leg radiograph, the case was included. 15 Exclusion criteria were inflammatory joint diseases or severe osteoporosis, previous high tibial osteotomy and septic lesion, severe obesity > 35 of body mass index, and severe bone defect > 10 mm. There was no case of arthroplasty for lateral compartment OA.…”
Section: Methodsmentioning
confidence: 99%
“…Stress radiographs were not available, however Waldstein et al . [21] reported that valgus stress radiographs provide no additional diagnostic information in lateral cartilage assessment in comparison to AP radiographs [3]. Data on Caucasian patients were derived from the literature and there was no matched comparative group in the current study [4].…”
Section: Discussionmentioning
confidence: 99%